Unravelling of Farmers’s Existing Crop Nutrient Management Practices - Chandra, N Hema Sarat; Ramulu, Ch; Swathi, G (Indian Journal of Extension Education, 2020)
Village adoption is a scientifically proven method for effective extension service to the farmers. The extension interventions in the village can be planned by considering the socio economical and agricultural situations prevailed in the village. An attempt was made to understand the existing crop nutrient management practices of the farmers in Seetharampuram village from Warangal Rural district of Telangana which stand selected by Regional Agricultural Research Station, Warangal (PJTSAU) to impart technical advices to the farmers. A semi structured interview schedule was prepared and soil samples were collected to analyse the existing crop nutrient management practices of the farmers. Soil analysis report from 203 samples were randomly collected by covering whole village fields and found that soils were neutral to strong alkaline in reaction (pH-7.0-9.06), non-saline to saline in nature (EC-0.30-2.95dS/m), low to medium (0.10-0.74%) organic carbon. Nitrogen was low to medium (88-339Kg/ha) phosphorus and potassium were medium to very high at 37-228Kg/ha and 297-1309Kg/ha respectively. Based on the responses from 60 randomly selected farmers in the village and considering soil analysis data, there was lot of discrepancy observed from recommended practices to the practices of farmers. Though crop yields were on par to the expectations but there was a lot of scope to reduce the chemical fertiliser usage and cost of cultivation. It was estimated that, Rs. 8,61,250/- can be saved to the village on soil nutrient management. Interventions towards sustainable agriculture, enhancing technical knowledge to the farmers and counter to depletion of soil nutrients are manifested as a part of technical empowerment in the adopted village.